Large-Scale Land Acquisitions, Livelihoods and Human Rights in South-East Asia - Christophe Gironde; Christophe Golay (Revue Internationale de Politique de Développement)
The various contributions to this volume show, first, that previous episodes of large-scale land acquisitions are crucial to an understanding of why, where and how the current wave is occurring; of how they are implemented and turned, or not, into production units; and of how and to what extent they affect livelihoods. This is valid even for those territories that have not encountered such episodes and where the creation of large estates is ‘new’. Second, beyond the usual emphasis on foreign companies, historical analysis also allows us to take stock of the key role played by nation states, which put in place regulatory frameworks and public policies or adopted a laissez-faire approach that paved the way for current land deals and acquisition practices around land and natural resources. Third, this volume highlights the importance of economic and political dynamics at local, national and sub-regional levels, which prove in South-East Asia to be as powerful as the global forces typically foregrounded in writings on ‘land grabbing’…